Self‐assessment sheet submission rate predicts technique survival in patients initiating peritoneal dialysis. Issue 6 (23rd February 2022) - Kusahana, Ei; Uchiyama, Kiyotaka; Yamaguchi, Nobuko; Hirashima, Maiko; Togashi, Tomoko; Yamamoto, Yuriko; Imai, Michiyo; Ashida, Mayumi; Yamamura, Keiko; Nakayama, Takashin; Yasuda, Itaru; Morimoto, Kohkichi; et al.
Abstract: Aim: Patients play a crucial role in preventing peritoneal dialysis (PD)‐related events, including peritonitis and fluid overload, as PD procedures are mainly carried out at home. We asked patients to submit a PD self‐assessment sheet at each outpatient visit in our daily clinical practice and evaluated its usefulness for outcomes in patients initiating PD. Methods: This retrospective cohort study included patients who underwent PD catheter insertion between January 2008 and October 2018. The submission rate of a PD self‐assessment sheet was calculated from medical records until PD cessation or study completion (October 2020). The association between the submission rate and technique survival was analysed. Results: Among the 105 recruited patients (78 men, 60.4 ± 12.2 years), 44 discontinued PD and transferred to haemodialysis during the study period. The follow‐up was 52.3 (28.7–79.3) months, and the median submission rate was 78%. The log‐rank test showed that technique survival was significantly better in patients with a submission rate ≥ 78% than those with a submission rate <78% ( p  = .006). The submission rate remained significantly associated with less technique failure (hazard ratio 0.88 per 10%, p  = .002) by the Cox regression analysis adjusted for age, sex, Charlson comorbidity index, estimated glomerular filtration rate and geriatric nutritional risk index. Conclusion: The submission rate of a PD self‐assessment sheet is useful as a predictor of technique survival in patients initiating PD. Instruction that increases submission may improve technique survival in PD patients. SUMMARY AT A GLANCE: This study shows that the submission rate of a PD self‐assessment sheet, which is probably an indicator of patients' adherence to therapy, predicts technique survival of incident PD patients initiating PD. The real challenge is how to improve patients' adherence and whether that would improve clinical outcome.